A short synthesis of d‐[1‐14C]‐serine of high enantiomeric purity. (27th February 2015) - Song, Fengbin; Salter, Rhys; Weaner, Larry E.
<x xml:space="preserve">Abstract</x> Herein, we report a short, three‐step synthesis of d‐[1‐14C]‐serine (4) in high enantiomeric purity. Starting from [14C]‐KCN and 2‐(benzyloxy)acetaldehyde, Strecker reaction using (R)‐1‐phenylethylamine as the chiral auxiliary gave two diastereomeric aminonitriles 1 and 2 in the ratio of 4:3, which were conveniently separated and purified chromatographically. Following hydrolysis and subsequent hydrogenolysis, the purified major diastereomer 1, was smoothly converted to d‐[1‐14C]‐serine (4) in an enantiomeric excess of >99%, thus circumventing time intensive chiral HPLC enantiomeric resolution.